Analisis Keandalan Produk Dengan Pola Penggunaan Intermittent - Farida D Sitania (ARIKA, 2010)
Reliability is probability that a product will perform a required function without any failures on certain operating conditions and at a certain time period. Most of the research on product reliability assumes that the product operates with a continuous pattern. In fact, in some situations the product usage patterns are intermittent. Examples of products with non-continuous usage patterns are an elevator, electric starter on a motorcycle, emergency generators, and others.